1999
DOI: 10.1074/jbc.274.35.24550
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-dependent Up-regulation of Human Somatostatin Receptor Type 1 Requires Molecular Signals in the Cytoplasmic C-tail

Abstract: We have previously reported that the human somatostatin receptor type 1 (hSSTR1) stably expressed in Chinese hamster ovary-K1 cells does not internalize but instead up-regulates at the membrane during continued agonist treatment (1 M somatostatin (SST)-14 ؋ 22 h). Here we have investigated the molecular basis of hSSTR1 up-regulation. hSSTR1 was up-regulated by SST in a time-, temperature-, and dose-dependent manner to saturable levels, in intact cells but not in membrane preparations. Although hSSTR1 was acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
51
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 30 publications
5
51
1
Order By: Relevance
“…However, the relationship between desensitization and receptor internalization was not examined in this cell line (35). In another study, the human sst1 receptor expressed in CHO-K1 cells was shown to desensitize after treatment with SRIF for 60 min when little receptor internalization had occurred (36,39). We show here that desensitization of the native rat sst1 receptor proceeds extremely rapidly in CHO-K1 cells, with a half-time less than 2 min.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…However, the relationship between desensitization and receptor internalization was not examined in this cell line (35). In another study, the human sst1 receptor expressed in CHO-K1 cells was shown to desensitize after treatment with SRIF for 60 min when little receptor internalization had occurred (36,39). We show here that desensitization of the native rat sst1 receptor proceeds extremely rapidly in CHO-K1 cells, with a half-time less than 2 min.…”
mentioning
confidence: 88%
“…Pretreatment of cells with SRIF leads to desensitization of both the rat and human sst1 receptor (35,39). In HEK cells expressing rat sst1-tag no effect was observed after a 10-min pretreatment with 1 M SRIF but significant desensitization occurred after preincubation for 30 and 120 min (35).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Exposure of agonists to G protein-coupled receptors frequently results in downregulation of the receptor transcript levels, but receptor upregulation has also been demonstrated (Siegrist et al 1994, Schanstra et al 1998, Froidevaux & Eberle 2002, Ankö & Panula 2006. Inoue et al (1999) found that calcitonin downregulates calcitonin receptor mRNA in mouse bone marrow cells and Dupre et al (2003) report the ligand-induced downregulation of the PAF-R. On the other hand, gene expression of the human somatostatin receptor type I is actively upregulated by somatostatin (Hukovic et al 1999). The regulation of CL/RAMP2 mRNA levels by AM in HMECs might reflect a physiological adaptation, which enables the cells to adjust the sensitivity of receptor-mediated processes by changes in receptor number, and, therefore, according to the level of receptor activation.…”
Section: K9mentioning
confidence: 99%
“…the rat sst 4 receptor appears to be largely resistant to agonist-induced internalization and desensitization (13), whereas the human sst 4 receptor has been reported to undergo a very slow but clearly detectable endocytosis. Other studies have shown that the human sst 1 receptor but not the rat sst 1 receptor failed to internalize in an agonist-dependent manner (14,15).…”
mentioning
confidence: 99%